Enhancing Mathematical Representation Skills through the MID Model: Does Cognitive Style Matter? - Santi Widyawati; Siti Qomariyah; Fredi Ganda Putra; Khoirunnisa Imama; Cahniyo Wijaya Kuswanto (FOUNDAE (Foundation of Advanced Education), 2025)
The ability to represent mathematical ideas is a fundamental component of mathematical understanding and communication. However, many students still struggle to express mathematical concepts in varied forms such as visual, symbolic, or verbal representations. This study aims to examine the effectiveness of the Meaningful Instructional Design (MID) learning model in improving students’ mathematical representation skills, while also considering the role of students’ cognitive styles. A quasi-experimental research design was implemented involving two groups: an experimental group taught using the MID model and a control group taught using conventional expository methods. The participants were selected using a cluster random sampling technique from a population of junior high school students. Data were collected through a validated mathematical representation test and a cognitive style questionnaire. The collected data were then analyzed using two-way ANOVA with a 5 percent level of significance, following prerequisite tests for normality and homogeneity using SPSS version 25 and Microsoft Excel. The results showed that students who learned through the MID model exhibited significantly higher mathematical representation skills than those taught using the expository model. Furthermore, students’ cognitive styles also had a significant main effect on their representation abilities. Despite these main effects, the interaction between the learning model and cognitive style was not statistically significant. These findings indicate that the MID model is a robust instructional approach that can enhance students’ mathematical representation skills across different cognitive style profiles. The study highlights the importance of adopting meaningful learning frameworks that prioritize concept-building and student engagement, regardless of learners’ individual differences.